Climate change, agriculture and food security: a comparative review of global modelling approaches - Dumollard, G.; Havlík, Petr; Herrero, Mario (2013)
The dual relationship existing between land-based activities and climate change has long been established. Land-based activities are responsible for about 30% (IPCC) of global GHG emissions and are at the same time particularly impacted by climate change as they are strongly dependent on weather patterns. Although physical and technical considerations may help to investigate these two kinds of issues, economic considerations are crucial to understand how agricultural producers react to climate change and to climate policies. Quantitative economic models are appropriate tools to examine these interactions and to understand how they influence human activities and ecosystems. However, there are many different economic models with different characteristics regarding the way economies are modelled, the way climate change is considered in the models and the way GHG emissions are accounted for. All these specificities determine the type of uses that each model can be employed for. This paper describes the different characteristics and uses of 13 economic models that are currently used to investigate issues concerning land-based activities and climate change.